INTEGRASI REMEDIASI MISKONSEPSI PESERTA DIDIK DENGAN MODEL PEMBELAJARAN ECIRR BERBANTUANPHET SIMULATION MOMENTUM DAN IMPULS DI SMA - Arifin, Ridwan; Tandililing, Edy; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to measure the effectiveness of integrated remediation by using the Elicit Confront Identify Resolve Reinforce (ECIRR) learning model in minimizing the number of student misconceptions in momentum material in impulses. Pre-experimental design with One Group Pretest-Posttest was used in this research. The population in this study was all students of class XI of State Senior High School 10 Pontianak. The Researcher took the intact Group research sample so that it could be obtained in the XI IPA 3 class which consisted of 29 students. The instrument of this study utilized a diagnostic test with 15 item in the from of multiple choice with open reasons. The magnitude of the percentage showed a decrease in the number of students who experience misconceptions with the ECIRR model on momentum and impulse material is 44%. The research also conducted the McNemar test with a significance level of 5% which showed that there had been a significant change in the conception of students after being given an integrative remediation activity using the ECIRR model. The ECIRR model was considered very effective in remediating student misconceptions in momentum material in impulses with an effectivity value of 0,429 with high category according to Hattie barometer. In conclusion, the ECIRR model was effective in reducingthe number of student misconceptions.Â Kata kunci: ECIRR, Integrasi, Miskonsepsi, Remediasi